Pengaruh Struktur Corporate Governance, Ukuran Perusahaan dan Kualitas Audit Terhadap Luas Pengungkapan Kompensasi Manajemen Kunci - Umarudin Kurniawan (Politeknik Kutaraja, 2021)
This study aims to study the role of the Corporate Governance (CG) structure that affects the level of mandatory disclosure of key management compensation in financial statements based on PSAK No.7 on Related Parties. The CG structures studied are family ownership, managerial ownership, audit committee, and other factors such as audit quality and company size on the level of disclosure of key management compensation in the financial statements. This research improves the measurement of managerial ownership variables. The sample of this research is banking companies listed on the Indonesia Stock Exchange in 2014 - 2016. Based on the results of the regression analysis, it shows that only two hypotheses (firm size and quality audit variables) are supported and three hypotheses (variable managerial ownership, family ownership, and audit committee effectiveness) are not supported.